ABUSE OF DOPING TO INCREASE STAMINA IN ATHLETES - Fernanda, Raihan Dinar; Elisa, Pirston; Yoga, I Made Ganda Juniartha (Indonesian Journal of Sports Law, 2024)
This research aims to determine efforts to prevent doping abuse in sports athletes. This is due to doping abuse, which without realizing it contains substances that are dangerous to health if used too often. This research uses qualitative descriptive research, which is a research method that utilizes qualitative data and is described descriptively. The aim of qualitative descriptive analysis is to describe in full and in depth the occurrence of various phenomena being analyzed. The results of this research are to increase knowledge in dealing with doping abuse among athletes, the effects of doping, and types of doping